2011
DOI: 10.1074/jbc.m111.257501
|View full text |Cite
|
Sign up to set email alerts
|

l-Ala-γ-d-Glu-meso-diaminopimelic Acid (DAP) Interacts Directly with Leucine-rich Region Domain of Nucleotide-binding Oligomerization Domain 1, Increasing Phosphorylation Activity of Receptor-interacting Serine/Threonine-protein Kinase 2 and Its Interaction with Nucleotide-binding Oligomerization Domain 1

Abstract: Commensal bacteria that colonize the human colon produce significant amounts of di/tripeptides. We were the first to report that PepT1 transports the small formylated bacterial peptide (fMLP) (1, 2). In the interval since that time, we have shown that other bacterial peptides, such as MDP 3 and Tri-DAP, may also be transported by hPepT1 (3, 4). Small bacterial peptides occur at substantially lower levels in the small intestine compared with the colon in line with the reduced numbers of prokaryotes present in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
71
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 83 publications
(74 citation statements)
references
References 37 publications
(37 reference statements)
0
71
1
Order By: Relevance
“…The study concluded that the Salmonella virulence factor SopE alters the activation of the RhoGTPases, Rac1 and Cdc42, which is sensed by NOD1 to induce NF-B-signaling by RIP2 (135). This model is inconsistent with recent studies providing evidence for a direct interaction between NOD1 and its ligand Tri-DAP (155). Future studies in RAC1-and Cdc42-deficient cells should be performed to address the strength of effectordriven immunity by NLRs in these models.…”
Section: B Other Signaling Transduction Pathwayscontrasting
confidence: 51%
“…The study concluded that the Salmonella virulence factor SopE alters the activation of the RhoGTPases, Rac1 and Cdc42, which is sensed by NOD1 to induce NF-B-signaling by RIP2 (135). This model is inconsistent with recent studies providing evidence for a direct interaction between NOD1 and its ligand Tri-DAP (155). Future studies in RAC1-and Cdc42-deficient cells should be performed to address the strength of effectordriven immunity by NLRs in these models.…”
Section: B Other Signaling Transduction Pathwayscontrasting
confidence: 51%
“…In contrast, NOD2 recognizes MDP, a PGN fragment that is found in Gram-negative and Grampositive bacteria alike (34) ( Table 1). The LRR region of NOD1 or NOD2 is essential for PGN detection (33,106), and recent evidence has revealed direct binding of these domains to PGN fragments (37,62,77). It is thought that direct binding of MDP or ieDAP leads to a conformational change of the LRR horseshoe structure and to homodimerization of the NLR via the NOD domain (56, 100).…”
Section: Noncanonical Inflammasomes and Intracellular Lps Sensingmentioning
confidence: 99%
“…Recent evidence suggests, albeit with certain caveats, that NOD1 and NOD2 do indeed directly sense their ligands (Monie, 2013). The first evidence of direct interaction was provided using the biophysical techniques atomic force microscopy and surface plasmon resonance to show that ie-DAP bound to immobilized commercially prepared NOD1 but that no interaction was detected between NOD1 and MDP or after removal of the NOD1 LRRs (Laroui et al, 2011). Although this provided some indication of interaction specificity and supported a critical role in ligand recognition for the LRRs of NOD1, a failure of NOD1 to interact with a wider range of small molecules would strengthen the interpretation of the data.…”
Section: Activation and Signal Transduction In The Nucleotide-bindmentioning
confidence: 99%